2004
DOI: 10.1021/jf034612p
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a High Concentration of Mineral or Vitamin into Chitosan-Based Films

Abstract: Mineral or vitamin E was incorporated into chitosan-based films: 10-200% (w/w chitosan) Gluconal Cal (GC), a mixture of calcium gluconate and lactate; 5-20% zinc lactate (ZL); and 5-20% alpha-tocopheryl acetate (VE) with acetylated monoglyceride (AM). The functionality of film-forming solutions and dried films was analyzed with standard procedures, and mathematical equations were developed to coordinate selected film functionality with the type and concentration of incorporated mineral or vitamin E. GC incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
144
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(162 citation statements)
references
References 19 publications
13
144
0
5
Order By: Relevance
“…Nessas condições, foi medida a absorbância em 600 nm. Os resultados foram apresentados como a razão entre a absorbância e a espessura do filme (mm) (Abs 600nm mm -1 ) [17] .…”
Section: Processamento De Filme Poliméricounclassified
“…Nessas condições, foi medida a absorbância em 600 nm. Os resultados foram apresentados como a razão entre a absorbância e a espessura do filme (mm) (Abs 600nm mm -1 ) [17] .…”
Section: Processamento De Filme Poliméricounclassified
“…In addition, chitosan is an excellent edible film component due to its film-forming capacity and good mechanical properties and can form transparent films, which can fulfill various packaging needs (Srinivasa et al 2002). As compared with other bio-based food packaging materials, chitosan-based films have also been claimed as effective carriers of many functional ingredients, such as antimicrobial agents and antioxidants to extend storage quality of food (Tripathi et al 2008, Pranoto et al 2005, Park and Zhao 2004. Chitosan films can be prepared by cross-linking with agylcone geniposidic acid (Mi et al 2006), ternary chitosanglucomann-nisin (Li et al 2006), blending of ferulic acid incorporated starch chitosan (Mathew and Abraham 2008), incorporation of garlic oil, potassium sorbate and nisin (Pranoto et al 2005), chitosan-potato starch film using microwave treatment (Tripathi et al 2008), starch/chitosan blend film under the action of irradiation (Zhai et al 2004) and water soluble chitosan and amylose film (Suzuki et al 2005) etc.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mei & Zhao (2003) evaluated the feasibility of milk protein-based edible films to carry high concentrations of calcium (5 or 10% w/v) and vitamin E (0.1% or 0.2% w/v). In contrast, Park & Zhao (2004) reported that the water barrier property of the chitosan-based films was improved by increasing the concentration of mineral (5-20% w/v zinc lactate) or vitamin E in the film matrix. Nevertheless, the tensile strength of the films was affected by the incorporation of high concentrations of calcium or vitamin E. Gómez-Estaca, Montero, Giménez, & Gómez-Guillén, (2007) studied the effect of functional edible film enriched with oregano or rosemary extract, a gelatinechitosan film-coating and/or high pressure processing on the microbiological and oxidative stability of cold-smoked sardine.…”
Section: Edible Films and Coatingsmentioning
confidence: 94%